Impacting Factors of Road Traffic Accidents in Kathmandu Valley - Manandhar, Raju Bhai; Timilsina, Jagat (Pragya Darshan प्रज्ञा दर्शन, 2023)
The major objective of the study is to investigate the relationship and impact of over speed, negligence, and poor vehicle conditions on road traffic accidents in Nepal. The study targeted drivers of two-wheeled and four-wheeled vehicles as a population. 100 respondents were selected through a simple random sampling technique based on the police report list during the last 5 years of Kathmandu Valley. Primary data was the source of information and was collected using a well-structured, five-point Likert scale survey. Cronbach's Alpha coefficients were used to examine the internal consistency of the factors and an independent sample t-test was adopted to analyze differences in road traffic accidents, over speed, overload, and poor vehicle condition in terms of gender. Mean, standard deviation, variance, and correlation were adopted to analyze the data systematically to derive the findings. The study found a relationship between speed and negligence in road traffic accidents in Kathmandu Valley. However, a strong relationship exists between poor vehicle conditions road traffic accidents. The study also found that gender has no impact on overload, poor vehicle conditions, and road traffic accidents, except negligence. The future researcher can study the impact of other independent variables on road traffic accidents targeting drivers of two-wheelers and four-wheelers with a large sample size in a broad area.